2020
DOI: 10.3390/nu12010191
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cdx2 Polymorphism on the Relationship between Dietary Calcium Intake and Peak Bone Mass in Young Japanese Women

Abstract: Studies investigating the effect of the caudal-type homeobox protein 2 (Cdx2) polymorphism in the vitamin D receptor gene and calcium intake on bone mass have shown inconsistent results. This study investigated whether the effect of calcium intake on peak bone mass is affected by Cdx2 polymorphism in young Japanese women. A cross-sectional study of 500 young women was conducted. Dietary intake was assessed by the Food Frequency Questionnaire. The osteo sono-assessment index (OSI), assessed by the qualitative u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 52 publications
0
3
0
1
Order By: Relevance
“…Ao que diz respeito sobre as variantes genéticas desse gene sabe-se que cinco são as mais conhecidas: FokI, BsmI, TaqI, ApaI e Cdx2, cada um localizado em uma região do gene e associado a alterações diferentes do receptor, podendo aumentar ou diminuir sua atividade. O polimorfismo Cdx2, por exemplo, é resultado da substituição de uma guanina por uma adenina na região promotora do gene, levando a transição do alelo G para o alelo A e com isso há um aumento da atividade transcricional do gene (Pulito et al, 2015;Valdiveso & Fernandez, 2006;Oono et al, 2020).…”
Section: Resultsunclassified
“…Ao que diz respeito sobre as variantes genéticas desse gene sabe-se que cinco são as mais conhecidas: FokI, BsmI, TaqI, ApaI e Cdx2, cada um localizado em uma região do gene e associado a alterações diferentes do receptor, podendo aumentar ou diminuir sua atividade. O polimorfismo Cdx2, por exemplo, é resultado da substituição de uma guanina por uma adenina na região promotora do gene, levando a transição do alelo G para o alelo A e com isso há um aumento da atividade transcricional do gene (Pulito et al, 2015;Valdiveso & Fernandez, 2006;Oono et al, 2020).…”
Section: Resultsunclassified
“…The present study evaluated the VDR genotypes, bone mass, and calcium intake in young Japanese women. As we have previously elucidated the relationship between bone mass and Cdx2 (rs11568820), a representative SNP of VDR genes [ 32 ], the present study focused on four representative VDR gene polymorphisms other than Cdx2 , including Bsm I (rs1544410), Taq I (rs731236), Apa I (rs7975232), and Fok I (rs2228570).…”
Section: Discussionmentioning
confidence: 99%
“…We previously reported that the relationship between dietary calcium intake and bone mass differs depending on the VDR Cdx2 genotype [ 32 ]. Furthermore, certain studies have implied that VDR genotypes modulate the calcium absorption rate [ 42 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…From our previous study, it was reported that the relationship between the VDR Cdx2 genotype and bone mass differs depending on dietary calcium intake (28). Furthermore, certain studies have implied that VDR genotypes modulate the calcium absorption rate (38)(39)(40).…”
Section: Discussionmentioning
confidence: 99%